Capitalising on conjunctures: Tesla’s ups and downs in financialised capitalism - Tobias Klinge; Stefan Ouma; Reijer Hendrikse (Finance and Society)
This article explores the puzzling ups and downs of Tesla, going through one the most volatile stock market swings of the recent past, under conditions of financialised capitalism. We adopt a conjunctural approach, highlighting both the macro and micro dynamics shaping the firm’s financial market trajectory. Among these, meticulously maintained narratives, boosted by social media, attracted dedicated followers, while the rise of new retail trading platforms and excitement around Tesla’s index inclusion helped in producing its stock ‘mementum’. This volatility was further supported by an exceptionally large volume of financial derivatives trading, paralleling a public battle between short sellers and the company’s defenders. The resulting stock market boom enabled Tesla to stabilise its finances, whilst its ‘mercurial’ CEO Elon Musk negotiated the largest executive compensation package in US corporate history, turning him into the world’s richest individual. In conclusion, we argue that Tesla serves as an emblematic case of an increasingly tech-driven financialised capitalism, which scholars could use as a window to study future conjunctures.